2018
DOI: 10.1017/s0954394518000145
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete neutralization in African American English: The case of final consonant voicing

Abstract: In many varieties of African American English (AAE), glottal stop replacement and deletion of word-final /t/ and /d/ results in consonant neutralization, while the underlying voicing distinction may be maintained by other cues, such as vowel duration. Here, I examine the relationship between vowel duration, final glottal stop replacement, and deletion of word-final /t, d/ to determine whether the phonological contrast of consonant voicing is maintained through duration of the preceding vowel. Data come from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(54 reference statements)
2
13
0
Order By: Relevance
“…North American dialects, in contrast, all have robustly positive VE values (no credible interval crosses the 0 line) and are generally larger than the British and Irish variants, shown by the position of red (North American) and blue (United Kingdom and Ireland) points respectively in Figure 2. In particular, the AAE dialects have the largest VEs in the sample, which are all robustly larger than the average "English" VE size (Rochester NY:β = 1.35, CrI = [1.27, 1.44]; Princeville NC:β = : this is consistent with previous studies of studies on AAE, which posit that final devoicing of word-final voiced obstruents results in compensatory vowel lengthening (Holt et al, 2016;Farrington, 2018). Turning to variability in VE across individual speakers, we observe that speakers are estimated to vary within-dialect by between 0.07 and 0.08 (σ speaker = 0.08, CrI = [0.07, 0.08]), meaning that speakers differ in their VE ratios by between 32 and 37% ( Table 3).…”
Section: Voicing Effect Across Dialects and Speakerssupporting
confidence: 86%
See 2 more Smart Citations
“…North American dialects, in contrast, all have robustly positive VE values (no credible interval crosses the 0 line) and are generally larger than the British and Irish variants, shown by the position of red (North American) and blue (United Kingdom and Ireland) points respectively in Figure 2. In particular, the AAE dialects have the largest VEs in the sample, which are all robustly larger than the average "English" VE size (Rochester NY:β = 1.35, CrI = [1.27, 1.44]; Princeville NC:β = : this is consistent with previous studies of studies on AAE, which posit that final devoicing of word-final voiced obstruents results in compensatory vowel lengthening (Holt et al, 2016;Farrington, 2018). Turning to variability in VE across individual speakers, we observe that speakers are estimated to vary within-dialect by between 0.07 and 0.08 (σ speaker = 0.08, CrI = [0.07, 0.08]), meaning that speakers differ in their VE ratios by between 32 and 37% ( Table 3).…”
Section: Voicing Effect Across Dialects and Speakerssupporting
confidence: 86%
“…In studies of the SVLR, some East Coast Scotland speakers show some evidence of the VE in production (Hewlett et al, 1999), whilst VE-like patterns were not observed in spontaneous Glaswegian (Rathcke and Stuart-Smith, 2016). On the other hand, studies of African American English (AAE) have claimed that voiced stops undergo categorical devoicing in this variety, which has resulted in additional vowel lengthing before voiced stops to maintain the pre-consonantal voicing contrast (Holt et al, 2016;Farrington, 2018). Only one study has previously compared the VE across English dialects in spontaneous speech.…”
Section: The Voicing Effect (Ve)mentioning
confidence: 99%
See 1 more Smart Citation
“…Jacewicz et al (2007), examining data from 54 speakers across Ohio, Wisconsin, and North Carolina, also reported both a significant VE effect and that the size of the significantly differed across three US English dialects, though point out that this effect is small relative to other phonetic factors (such as vowel height). Holt et al (2016), examining vowel variability in African American English (AAE) speakers in North Carolina, showed that vowels preceding voiced stops are longer in AAE than White American English (WAE) speakers in order to account for variable devoicing of final voiced consonants: for AAE speakers, the cue for final voicing has shifted to vowel duration to compensate for the neutralisation of voicing of the stop (Farrington 2018). As it is suggested that this duration compensation is triggered by the devoicing of stops, it is not clear whether equivalent voiced-voiceless durational differences should be expected for fricatives or affricates.…”
Section: The Voicing Effect (Ve)mentioning
confidence: 99%
“…2 After grouping, regions with 5 or fewer speakers were excluded in order to provide more reliable estimates for dialects kept in the sample. As ethnicity is expected to play a large role in particular VE patterns within certain dialects (Holt et al 2016;Farrington 2018), having speakers of differing ethnicities within the same dialect group could result in misleading VE values. Thus, all non-white AE speakers were excluded from Santa Barbara (72 speakers), leaving the Washington DC speakers from the CORAAL corpus as the only AAE speakers in the analysis.…”
Section: Datamentioning
confidence: 99%